Retrospective Study of Chronic Coughing in Dogs in a Referral Centre in the UK: 329 Cases (2012–2021) - Carla Asorey Blazquez; Ico Jolly Frahija; Arran Smith; Rachel Miller; Mayank Seth; Edgar Garcia Manzanilla; Ferran Valls Sanchez (Animals)
Chronic coughing is a common complaint in small animal medicine and it has an extensive differential diagnosis with very different treatment and prognosis. Coughing is considered chronic when it lasts at least 8 weeks. This retrospective study aimed to describe the most common causes of chronic coughing in a population of dogs that presented to a referral hospital in England between January 2012 and December 2021. In addition, we aimed to evaluate if an association with signalment, weight, coughing characteristics, and/or concomitant clinical signs could be identified. A total of 329 dogs met the inclusion criteria. The most frequent diagnoses were airway collapse (102/329, 30.7%), chronic bronchitis (80/329, 24.3%), neoplasia (62/329, 18.8%), and infectious bronchopneumonia (54/329, 16.4%). Other diagnoses were also identified in a lower number of cases. Pomeranian, Chihuahua, and Yorkshire Terrier were over-represented breeds for airway collapse. No predictive factors were identified for chronic bronchitis. Lower body weight (odds ratio [OR] 0.92, 95% confidence interval [CI]: 0.90–0.95), non-productive (OR 14.3 CI 3.44–50) paroxysmal coughing (OR 4.9, 95%, CI: 2.2–11.0), and exercise intolerance (OR 3.3, 95%, CI: 1.7–6.3) increased the odds of airway collapse. Older dogs (OR 1.025, 95%, CI: 1.014–1.036), higher body weight (OR 1.048, 95%, CI: 1.018–1.080), lethargy (OR 5.1, 95%, CI: 1.5–17.7), haemoptysis (OR 8.6, 95%, CI: 1.9–38.4), weight loss (OR 4.0, 95%, CI: 1.1–15.3), and inappetence (OR 6.5, 95%, CI: 1.9–22.1) increased the odds of neoplasia. Productive coughing (OR 3.0, 95%, CI: 1.5–6) and nasal discharge (OR 4.1, 95%, CI: 1.4–11.9) were predictive factors of infectious bronchopneumonia. Younger age (OR 0.96, 95%, CI: 1.061–1.150), higher body weight (OR 1.097, 95%, CI: 1.037–1.161), and haemoptysis (OR 11.8, 95%, CI: 1.8–78.5), increased the odds of airway foreign body. Higher body weight (OR 1.105, 95%, CI: 1.061–1.150), older age (OR 1.041, 95%, CI: 1.022–1.061), and regurgitation were predictive factors of laryngeal paralysis. Epiglottic retroversion was associated with younger age (OR 0.969, 95%, CI: 0.943–0.994), dysphagia (OR 42.5, 95%, CI: 4.7–382.7), and regurgitation (OR 11.6, 95%, CI: 1.2–113.1). All the aforementioned findings are valuable for prioritising differential diagnoses and consequently increasing the efficacy of the diagnostic plan and prioritising tests, which becomes even more important in cases where financial constraints are present. Finally, an appropriate selection of diagnostics tools helps optimise veterinary resources.